2023
DOI: 10.1007/s00167-023-07410-2
|View full text |Cite
|
Sign up to set email alerts
|

Latarjet procedure for failed Bankart repair provides better stability and return to sports, but worse postoperative pain and external rotation limitations with more complications, compared to revision Bankart repair: a systematic review and meta-analysis

Abstract: PurposeThis study aimed to compare the clinical results of revision Bankart repair versus the Latarjet procedure for failed Bankart repair. MethodsA literature search was performed in databases, such as Pubmed, Embase, and Scopus Library. The studies were appraised using the Methodological Index for Non‐randomized Studies tool. Studies for failed Bankart repair with revision Bankart repair or Latarjet procedure were included. The pain VAS, ROWE score, rate of return to sports and preinjury level of sports, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…Our review found that both Bankart and Latarjet techniques significantly enhanced patient outcomes preand post-operatively. Our analysis aligns with Lho et al's findings that Latarjet have shown promising results compared to Bankart in terms of reduced instability and improved Rowe scores [6]. Our systematic review found the Latarjet is a superior for recurrent instability following a Bankart repair.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our review found that both Bankart and Latarjet techniques significantly enhanced patient outcomes preand post-operatively. Our analysis aligns with Lho et al's findings that Latarjet have shown promising results compared to Bankart in terms of reduced instability and improved Rowe scores [6]. Our systematic review found the Latarjet is a superior for recurrent instability following a Bankart repair.…”
Section: Discussionsupporting
confidence: 90%
“…Bone block procedures have traditionally been reserved for more severe instability with significant bone loss. The Latarjet procedure is indicated for recurrent instability, failed prior surgery, contact athlete, critical glenoid bone loss, and bipolar bone loss resulting in an off-track lesion [6]. Finally, free flap glenoid bone grafting such as the Eden-Hybinette procedure is indicated for critical bone loss and failed prior Latarjet procedure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent anterior instability of the glenohumeral joint that is accompanied by glenoid bone loss remains a challenge for shoulder surgeons [20,24]. Improperly addressed glenoid deiciency has been identiied as a main risk factor for failure of soft tissue stabilization methods of the shoulder [35].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior shoulder instability often requires surgical treatment, particularly in young athletes who wish to resume sports [3, 46, 50]. The most common surgical treatments involve either labral or capsular repair in shoulders with no glenoid defects [34, 51], or bone‐block procedures in shoulders with glenoid defects [13, 26, 35]. The Latarjet technique is among the most popular bone‐block procedures, as it proved effective at preventing recurrent dislocations [1, 2, 12, 21, 25, 27, 39] whether performed as an open or an arthroscopic procedure [15, 33].…”
Section: Introductionmentioning
confidence: 99%